Clinical reasoning in oncoplastic surgery at Plastic Surgery and Caumatology residents - Tatiana Hernandez González; Marta Alfonso Nazco; Miguel Angel Amaró Garrido; Ana Lucía Martínez Hernández; Eliecer González Valdez; Jorge Félix Jiménez Álvarez; Yurisbel Tomás Solenzal Alvarez (Gaceta Médica Espirituana)
Background: The medical specialist training based on competences is a necessity because society demands competent professionals, capable to use the scientific universe as a function of the economic, political and social development in the place where they work.